IMPLEMENTASI KONTROL DAN MONITORING AIR CONDITIONER STANDING FLOOR DAN CCTV BERBASIS IOT DI GEDUNG AUDITORIUM POLITEKNIK PENERBANGAN MEDAN - Bakkara, Natanael Riansa; Wimatra, Ayub; Ulum, Zahrul (Smart Education, 2025)
Abstract: This study discusses the implementation of a control and monitoring system for Standing Floor Air Conditioners (AC) and CCTV based on the Internet of Things (IoT) at the Auditorium of Medan Aviation Polytechnic. The research background stems from the high electricity consumption of AC units operated manually without an integrated monitoring system, which often leads to energy waste when the AC remains on in an unoccupied room. The proposed solution integrates a Smart Miniature Circuit Breaker (Smart MCB) and CCTV with the Tuya Smart platform, enabling real-time AC control via a Smartphone application, automated scheduling, and remote visual monitoring of room conditions. The research method applies an R&D approach using the ADDIE development model, which includes analysis, design, development, implementation, and evaluation. The designed system can display AC ON/OFF status and power consumption in real time, send disturbance notifications, and allow remote control. Testing results show a reduction in electricity consumption after system implementation, as well as improved monitoring effectiveness and room security. This system increases energy efficiency, reduces operational costs, and enhances building security. The study also serves as a reference for the development of IoT-based electrical technology in other public facilities. Keywords: Internet of Things, Tuya Smart, Smart MCB, Standing Floor AC, Energy Efficiency. Abstrak: Penelitian ini membahas implementasi sistem kontrol dan monitoring Air Conditioner (AC) Standing Floor serta CCTV berbasis Internet of Things (IoT) di Gedung Auditorium Politeknik Penerbangan Medan. Latar belakang penelitian didasari oleh tingginya konsumsi energi listrik pada AC yang dioperasikan secara manual tanpa sistem pemantauan terintegrasi, sehingga sering terjadi pemborosan energi ketika AC tetap menyala di ruang kosong. Solusi yang dikembangkan adalah integrasi Smart Miniature Circuit Breaker (Smart MCB) dan CCTV dengan platform Tuya Smart, yang memungkinkan pengendalian AC secara real-time melalui aplikasi Smartphone, penjadwalan otomatis, serta pemantauan visual kondisi ruangan dari jarak jauh. Metode penelitian menggunakan pendekatan R&D dengan model pengembangan ADDIE yang mencakup analisis, desain, pengembangan, implementasi, dan evaluasi. Sistem yang dirancang mampu menampilkan status ON/OFF dan konsumsi daya AC secara real-time, memberikan notifikasi gangguan, serta mengizinkan kontrol jarak jauh. Hasil pengujian menunjukkan adanya penurunan konsumsi daya listrik setelah implementasi sistem, serta peningkatan efektivitas pengawasan dan keamanan ruangan. Dengan adanya sistem ini, efisiensi energi meningkat, biaya operasional berkurang, dan keamanan gedung lebih terjamin. Penelitian ini juga menjadi acuan bagi pengembangan teknologi kelistrikan berbasis IoT di fasilitas publik lainnya. Kata kunci: Internet of Things, Tuya Smart, Smart MCB, AC Standing Floor, Efisiensi Energi.